1963
DOI: 10.1111/j.1438-8677.1963.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Numbers of Flowering Plants in the Netherlands

Abstract: 154 plant species, chosen at random, and collected in the Netherlands were investigated cytologically. The chromosome numbers determined were compared with data known from other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
42
0
3

Year Published

1965
1965
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 110 publications
13
42
0
3
Order By: Relevance
“…1E) is reported for the fi rst time from India and is in line with the previous chromosomal reports from outside India by Manton (1932), Gadella and Kliphuis (1966), Holmgren (1971) and Laane (1971).…”
Section: Capsella Bursa-pastoris (L) Mediksupporting
confidence: 78%
“…1E) is reported for the fi rst time from India and is in line with the previous chromosomal reports from outside India by Manton (1932), Gadella and Kliphuis (1966), Holmgren (1971) and Laane (1971).…”
Section: Capsella Bursa-pastoris (L) Mediksupporting
confidence: 78%
“…2i). The 4x cytotype with similar type of meiotic behavior has also been reported by different workers from India (Mehra et al 1965, Kumar 1982, Gupta and Gill 1984a, 1989) and outside of India (Tahara 1915, 1921, Tischler 1934, Cooper and Mahony 1935, Negodi 1937, Rohweder 1937, Löve and Löve 1956, Gadella and Kliphuis 1963, 1966, Engelskjon 1979, Van Loon and Kieft 1980. The species is also known to have diploid cytotype with 2n=18 (Gadella and Kliphuis 1963, Mehra et al 1965, Taylor and Mulligan 1968, Engelskjon 1979, Kumar 1982, Gupta and Gill 1984a, 1989 6x, 2n=54 (Dowrick 1952, Böcher and Larsen 1957, Mulligan 1958) and 8x, 2n=72 (Favarger 1963) cytotypes.…”
Section: Chrysanthemum Leucanthemum Linnmentioning
confidence: 76%
“…Based on x=12, the presently studied individuals exist at 2x level. The species which has been counted chromosomally for the first time from India adds a new cytotype (2x) to the already existing polyploid chromosome counts of 2n=60 (Langlet 1936, Delay 1947, Löve and Löve 1956, Gadella and Kliphuis 1966, Knaben and Engelskjøn 1967, Leveque and Gorenflot 1969, Májovský 1970, Loeve and Kjelloqvist 1974, Van den Brand et al 1979, Arohonka 1982, Dmitrieva and Parfenov 1985, Kuzmanov et al 1986, Kapoor et al 1987, Hill 1989, Parfenov and Dmitrieva 1988, Hollingsworth et al 1992 Lövkvist and Hultgard 1999, Probatova et al 2001) and 2n=72 (Hagerup 1941) from outside of India. Perusal of earlier chromosomal data and present investigations revealed that out of the 42 presently analyzed species, as many as 18 species (42.85%) exist at different ploidy levels.…”
Section: Tussilago Farfara Linnmentioning
confidence: 99%
“…There are no other chromosome number reports from North America. Several authors report 2n = 28 for Eurasian material (Tuschnjakowa 1929;Maude 1940;Ehrenberg 1945;Skalinska and Piotrowicz 1961;Gadella and Kliphuis 1973;Murin 1976;Löve 1980;Dvorak 1989). In summarizing information on chromosomes of H. morsus-ranae, Cook and Lüönd (1982) note that it possessed one pair of long sub-metacentric chromosomes, the rest being of medium length, metacentric, acrocentric, or short metacentric.…”
Section: Namementioning
confidence: 99%